2013
DOI: 10.2169/internalmedicine.52.0046
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Analysis of Glomerulopathy with Fibronectin Deposits (GFND): A Case of Sporadic, Elderly-Onset GFND with Codeposition of IgA, C1q, and Fibrinogen

Abstract: A 67-year-old Japanese man with recurrent nephrotic syndrome and impaired kidney function had a sporadic, elderly-onset case of glomerulopathy with fibronectin deposits. The daily urinary protein, serum albumin, blood urea nitrogen, and creatinine levels were 3.6 g/day, 2.7 g/dL, 19.5 mg/dL, and 1.70 mg/dL, respectively. Kidney biopsy samples were evaluated using electron microscopy and demonstrated membranoproliferative glomerulonephritis-like lesions with massive subendothelial depositions and no fibrillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…However, a better understanding of the genetic basis of the diseases has prompted a better classification of BFH into a number of rare glomerulopathies, such as MYH9-associated kidney disease, giant fibronectin glomerulopathy, C3/CFHR5 glomerulonephritis, immunotactoid glomerulonephritis and fibrillary glomerulonephritis. The renal outcome of these entities is worse than was initially described for BFH [47,[72][73][74][75][76].…”
Section: Recently Described Glomerulopathiesmentioning
confidence: 89%
“…However, a better understanding of the genetic basis of the diseases has prompted a better classification of BFH into a number of rare glomerulopathies, such as MYH9-associated kidney disease, giant fibronectin glomerulopathy, C3/CFHR5 glomerulonephritis, immunotactoid glomerulonephritis and fibrillary glomerulonephritis. The renal outcome of these entities is worse than was initially described for BFH [47,[72][73][74][75][76].…”
Section: Recently Described Glomerulopathiesmentioning
confidence: 89%
“…Deposition of immunoglobulins or complement components in the glomeruli is a commonly observed phenomenon in immunofluorescent study. Yoshino et al ( 15 ) reported detection of immunoglobulin, fibrinogen, or complement components in 15 of their 43 cases (35%) ( 16 ). The link between immunoglobulin or complement component deposition and prognosis has not been clearly defined.…”
Section: Discussionmentioning
confidence: 99%
“…Its mutations altered the proteindimers assembly into fibrils in the extracellular matrix and produce a disbalance between soluble and insoluble fibronectin, leading to its pathognomonic deposition in mesangium and subendothelial area [66,67] . In addition to fibronectine deposition, it has been reported IgA, C1q and fibrinogen deposits [68] . GFND may present at different ages, although mostly in adolescence or early adulthood.…”
Section: Fibril Deposit Diseasementioning
confidence: 99%